IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) DI DESADATARNANGKA KECAMATAN SAGARANTEN KABUPATEN SUKABUMI - Muhammad Irfan Habibi (Jurnal Dialektika Politik, 2023)
This research follows Edward III's theory from Anggara (2018: 250) which identifies key implementation variables: communication, resources, disposition, and bureaucratic structure. The main premise is that the successful implementation of the Child Identity Card Policy in Datarnangka Village, Sagaranten Sub-district, Sukabumi District depends on clear communication, adequate resources, disposition of implementers, and a flexible bureaucratic structure. Field results show that communication is not optimal, resources are limited, disposition is not maximized, and the bureaucratic structure needs adjustment. This research was located in Datarnangka Village, involving 6 informants from the UPTD of Sagaranten region, the Head of Datarnangka Village, the Head of the Village Service Section, and residents. Data were collected through observation, interviews and document study using observation guides, interview guidelines and field notes. Validity was asserted through triangulation, while analysis was conducted using a reduction process. The findings show the importance of implementation factors. Implementation of the Child Identity Card Policy has not been optimal, related to communication, limited resources, disposition has not been maximized, and the bureaucratic structure needs improvement in the future.